2012
DOI: 10.1103/physrevlett.108.076101
|View full text |Cite
|
Sign up to set email alerts
|

Structures, Energetics, and Dynamics of Helium Adsorbed on Isolated Fullerene Ions

Abstract: Helium adsorbed on C 60 þ and C 70 þ exhibits phenomena akin to helium on graphite. Mass spectra suggest that commensurate layers form when all carbon hexagons and pentagons are occupied by one He each, but that the solvation shell does not close until 60 He atoms are adsorbed on C 60 þ , or 62 on C 70 þ . Molecular dynamics simulations of C 60 He n þ at 4 K show that the commensurate phase is solid. Helium added to C 60 He 32 þ will displace some atoms from pentagonal sites, leading to coexistence of a regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
134
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 71 publications
(149 citation statements)
references
References 31 publications
14
134
1
Order By: Relevance
“…These 'magic numbers' have been previously observed by our group in the studies of positively charged fullerene-helium complexes [11]; those data are included in Figure 2 as open dots. For n < 60, the size dependences of anions and cations are quite similar although there is more scatter in the anion data, probably due to poorer statistics.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…These 'magic numbers' have been previously observed by our group in the studies of positively charged fullerene-helium complexes [11]; those data are included in Figure 2 as open dots. For n < 60, the size dependences of anions and cations are quite similar although there is more scatter in the anion data, probably due to poorer statistics.…”
Section: Resultsmentioning
confidence: 77%
“…In a series of experiments we have recently studied the adsorption of helium [11] and several molecular gases [12] on isolated C + 60 and C + 70 cations. Mass spectra indicate a strong energetic preference for formation of the 1 × 1 phase in which the 12 pentagons plus 20 hexagons of C 60 (25 hexagons for C 70 ) are decorated with one particle each.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of the decoration of both C60 + and C60 -by helium have been reported, as well as the equivalent ions for C70. 9,10 In these experiments the fullerene molecules were first isolated in liquid helium nanodroplets and then subjected to electron bombardment, either at low energy (for anions) or higher energy (for cations). The mass spectra show enhanced abundances for ions with extra stabilities which are often referred to as magic number ions.…”
mentioning
confidence: 99%